Re-Examining the Nexus between Exchange and Interest Rates in Nigeria - Oke, David Mautin; Bokana, Koye Gerry; Shobande, Olatunji Abdul (Journal of Economics and Behavioral Studies, 2018)
Nigeria has experienced somersault of foreign exchange policies by the Central Bank. One policy concern in recent times is to have an appropriate target of the exchange and interest rates. Therefore, this paper seeks to provide a foundation for the targeting of an appropriate exchange and interest rates for the country. Using the Johansen Cointegration and Vector Error Correction Mechanism approaches, it specifically examines the relationships among Nigeria’s weak exchange rate, its local rate of interest and world interest rate. Contrary to many studies, a control measure involving inclusion of inflation, money supply and national output in the model is done. The analysis showed an equilibrium association between exchange rate and interest rate-cum-other variables and steady rectification of deviance from long-run stability over a sequence of incomplete short-run modifications. Increase in domestic and world interest rate, inflation, money supply and GDPat equilibrium would strengthen the exchange rate. Besides, further findings showed some bidirectional causal associations among the variables. By long-run implication, the targeting of an appropriate exchange rate in Nigeria requires a tightened monetary policy that is not inflation and growth biased. However, increase in world interest rate, money supply and inflation rate must be moderate in order not to worsen the exchange rate as suggested by the short-run result.